Evaluation of mean platelet volume / platelet count ratio in hyperemesis gravidarum - filiz halici ozturk; ayse kirbas; ahmet erol; Yaprak Engin-Ustun (Medicine Science, 2019)
Objectives: To investigate whether serum levels of inflammatory markers including high sensitive C-reactive protein (hs-CRP) and mean platelet volume (MPV) to platelet count ratio (MPR) were altered in patients with hyperemesis gravidarum (HEG) compared to asymptomatic pregnant women.